An assessment of the storage conditions of live, attenuated vaccines against measles, in authorized vaccination centers and in health services in S. Paulo State (Brazil) - Mendes, Inácio França; Pral, Michel Marie; Miyaki, Cosue; Gallina, Neuza Maria Frazatti; Petricevich, Vera Lucia; Fang, Francisco Liauw Woe; Tuchiya, Hiroko Nakahata; Ninomya, Tuyoshi; Rizzo, Edda de (Revista de Saúde Pública, 1985)
In the State of S. Paulo, Brazil, health centers sponsored by the State, as well as private health services, located in throughout large districts, are in charge of the vaccination against the various diseases affecting children, including measles. In the present study three of the above mentioned districts, covering 385 State Health Centers (SHC) and 200 Private Health Services (PHS) were surveyed. From these totals 117 SHC and 71 PHS were chosen for the evaluation of: a) quality of the existing cold chain for measles vaccine storage (temperatura); b) vaccine titer; c) validity; d) protection from light. Of the SHC inspected, 85.33% kept vaccines at the recommended temperature, 100% presented vaccines with titers above the minimum required and within expiration date. Deficiency relating to protection from light, was found in 83.06%. Inspection of the PHS revealed that whereas 66.20% kept vaccine within the right temperature range, 76.06% did not protect them against light, only 96.47% had vaccines with potency above the level required and only 85.51%, observed the expiration date. The study led to the conclusion that in the State of S. Paulo, measles vaccines are better stored in the State Health Centers than in the Private Health Services surveyed indicating that the slight preference that parents show towards having their children vaccinated in PHS is not justified. It was suggested that some conditions of measles vaccine storage montly, temperature and protection from light should be improved and that instruction leaflets must always accompany immunobiological materials distributed to all health centers, to be consulted when doubts about the proper storage and administration of these vaccines arise.